The Antidepressant-Like Effects of Shen Yuan in a Chronic Unpredictable Mild Stress Rat Model - Jiang, Ning; Wang, Haixia; Huang, Hong; Lv, Jingwei; Zeng, Guirong; Wang, Qiong; Bao, Yu; Chen, Ying; Liu, Xinmin (Frontiers in Psychiatry, 2021)
Depression is a common yet severe neuropsychiatric condition that causes imposes considerable personal, economic, and social burdens worldwide. Medicinal plant species (e.g., Panax ginseng and Polygala tenuifolia) demonstrate potent antidepressant-like effects with less toxicity and other side effects. Shen yuan prescription (SY), composed of Panax ginseng (GT) and Polygala tenuifolia (YT). The present study aimed to elucidate the effects of SY treatment on chronic unpredictable mild stress (CUMS) rats and study the underlying mechanism. Our results indicated that SY (67.5, 135 or 270 mg/kg) significantly reverses the depressive-like behaviors in rats with a five-week CUMS exposure, as demonstrated by increased sucrose consumption in the sucrose preference test, and decreased immobility time in the tail suspension and forced swim test. Moreover, SY altered serum corticosterone levels, proinflammatory cytokines (IL-6, IL-1β, and TNF-α), and oxidative markers (SOD, CAT, and MDA), and increased the levels of hippocampal neurotransmitters (5‐HT, DA, and NE) in rats exposed to CUMS. Furthermore, rats treated with SY showed a reduction in the protein expression of BDNF, p‐TrkB, p‐Akt, and p‐mTOR proteins induced by CUMS exposure in the hippocampus. In conclusion, SY prevented depressive-like behaviors in CUMS-exposed rats by preventing hypothalamus-pituitary-adrenal axis dysfunction, decreasing the levels of the neurotransmitters, minimizing oxidative stress, suppressing neuroinflammation, and activating the PI3K/Akt/mTOR‐mediated BDNF/TrkB pathway, all of which are the key players in the pathological basis of depression.